ChemInform Abstract: Metal‐Free Enantioselective Electrophilic Activation of Allenamides: Stereoselective Dearomatization of Indoles. Issue 19 (May 2015) - Romano, Ciro; Jia, Minqiang; Monari, Magda; Manoni, Elisabetta; Bandini, Marco
Abstract: The reaction can be applied in a one‐pot dearomatization/hydrogen‐transfer cascade reaction giving trans‐indolines (XII) in good yields and with high stereoselectivities.